Hypercapnia from Physiology to Practice - Amilkar Almanza-Hurtado; Camilo Polanco Guerra; María Cristina Martínez-Ávila; Diana Borré-Naranjo; Tomás Rodríguez-Yanez; Carmelo Dueñas-Castell (International Journal of Clinical Practice)
Acute hypercapnic ventilatory failure is becoming more frequent in critically ill patients. Hypercapnia is the elevation in the partial pressure of carbon dioxide (PaCO2) above 45 mmHg in the bloodstream. The pathophysiological mechanisms of hypercapnia include the decrease in minute volume, an increase in dead space, or an increase in carbon dioxide (CO2) production per sec. They generate a compromise at the cardiovascular, cerebral, metabolic, and respiratory levels with a high burden of morbidity and mortality. It is essential to know the triggers to provide therapy directed at the primary cause and avoid possible complications.